Qualitative techniques to investigate how patients evaluate dentists: a pilot study - Newsome PRH, Wright GH (Blackwell Synergy, 2000)
Most previous studies have portrayed patient satisfaction as a rather simple outcome based solely on patient perceptions. The goal of this pilot study was to determine if evidence could be found to support the view that patient evaluation is a more complex process better explained by drawing on the theories of ‘disconfirmation of expectations’ and ‘attribution’. Methods: A qualitative methodological approach was chosen with data collection being achieved by means of four focus group interviews comprising a total of 25 participants (16 women and 9 men, mean age 43.8 years, standard deviation of 14.45) representing a wider population of adults (over the age of 18) who had attended for dental treatment within the previous 12 months.